Significance of Individualized Choice of Vocal Role-Model for Vocal Training of Young Singers - Krīgere, Zigrīda (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The article addresses one of vocal coaching problems – individualized approach for young singers when choosing vocal role-model. Author states that this topic is not sufficiently explored in Latvia. The interest has been stimulated by a performance heard by the author. This performance left the author deeply impacted and even created a desire to copy it. These first impressions were the basis on which a singer can build up his or her personal aesthetics or develop his vocal role-model. Article contains autobiographical artist experiences, interview with opera singer K. Zarinu and academic reports on intuition, empathy, idiomotorics. During the course of the research author has employed methodical materials, personal experience and observations from pedagogical practice.